Does Previous Surgical Training Impact the Learning Curve in Video-Assisted Thoracic Surgery Lobectomy for Trainees? - Billè, Andrea; Okiror, Lawrence; Harrison-Phipps, Karen; Routledge, Tom (The Thoracic and Cardiovascular Surgeon, 2016)
Background To analyze if the number of open lung resections performed by trainees before starting video-assisted thoracic surgery (VATS) lobectomy training program has any impact on intraoperative and postoperative outcomes.Materials and Methods Retrospective analysis of 46 consecutive patients who underwent VATS lobectomies between December 2011 and September 2012 by two trainees (A.B. and L.O.). The previous surgical experience of the two trainees was evaluated to assess for any difference in terms of learning curve. Group A comprised 25 VATS lobectomies performed by one trainee (A.B.) and group B comprised 21 VATS lobectomies performed by the other trainee (L.O.).Results There was no statistical difference in terms of operating time and intraoperative bleeding between the two groups (p = 0.16 and p = 0.6). The conversion rate was 8% (2 out of 25 cases) in group A and 23.8% (5 out of 21 cases) in group B (p = 0.002). Evaluation of vascular injury showed no difference in the conversion rate (p = 0.56). The median length of the drainage and of hospital stay were 4 days and 7 days in group A and 4 days and 8 days in group B, respectively (p = 0.36 and p = 0.24). The complication rate was 44% in group A and 47.6% in group B (p = 0.52). A.B. had performed 139 and L.O. 70 operations as first operator before starting their VATS lobectomy training; the surgical experience had an impact only on the conversion rate.Conclusion Our study showed that a training program in VATS lobectomy is feasible, and previous surgical training has a minimal impact on intraoperative and postoperative outcomes.
Keywords: VATS lobectomy; learning curve; training program